Spaces of fractions and positive functionals - Vasilescu, F.-H. (MATHEMATICA SCANDINAVICA, 2005)
We discuss integral representations and extensions of positive functionals in some spaces of fractions of continuous functions. As a consequence, numerical caracterizations for the solvability of power moment problems and the uniqueness of the solutions in unbounded sets are obtained.